How Does Ecological Migration Drive Land Use in Resettlement Areas? Taking the Shule River Resettlement Project as an Example - Liao, Ting; Wang, Lucang (International Journal of Natural Resources and Environmental Studies, 2025)
Eco-migration is a special migration formed to improve the habitat environment and alleviate the ecological pressure, which is an important initiative to realize the United Nations sustainable development goals, and a livelihood project to promote the harmonious coexistence of human-land relationship. Due to the external migration of large-scale immigrants, it leads to abrupt and special land use changes in resettlement areas compared with general areas. [Model] This paper systematically studies the impact of the Shule River resettlement project on land use change by comprehensively applying the land use transfer matrix, information entropy, and the human activity intensity index model with the support of land use data from 1996 to 2010. [Results] The study found that: 1. The change process of land use reflects the change process from micro-change→dramatic change→smooth change in the early stage of migration→middle stage of migration→end stage of migration, and reflects the order of priority needs of life→production→ecology. 2. In the early and middle stages of migration, the grassland is mainly transformed into arable land and construction land, and in the end stage, when the migrants realize the basic “living and working in peace and contentment”, they begin to pay attention to the optimization of the living environment, and the amount of forest land increases. 3.The entropy of land use structure information and the degree of balance are both on the rise, and are closely related to the resettlement mode and scale of immigrants, with large-scale immigrant resettlement bases tending to be more diversified and balanced. On the contrary, the degree of dominance shows a decreasing trend, indicating that with the migration process, land use has gradually moved from purely favoring production (construction land) and production (arable land) to taking ecology into account. 4. The migration process is projected on the human activity intensity index, which shows stage and spatial heterogeneity. There is a significant positive correlation between the rise and fall of the human activity intensity index in the project implementation period and the intensity of migration, and the larger the scale of migration, the greater the intensity of human activities and the stronger the shaping effect on land use. [Conclusion] Ecological migration is the dominant force driving land use change.